Genetic expression of heterosis for yield and quality traits during different growing seasons in okra (Abelmoschus esculentus) - SOLANKEY, S S; SINGH, ANIL K; SINGH, R K (The Indian Journal of Agricultural Sciences, 2026)
The trial was conducted during summer and rainy seasons of 2006-2008 at the Institute of Agricultural Sciences, BHU, Varanasi. Appreciable heterosis over better parents of 51 F1’S of okra (Abelmoschus esculentus (L.) Moench] was recorded for various horticultural traits and quality traits over both the seasons. It was confounded that rainy seasons was more yield productive seasons than summer. The colour pigment expressed that the reddish green pod colour was dominant over green and purple green pod colour in F1’s crosses due to additive gene effects. The high fruit yield potential and quality attributing traits recorded in the F1 hybrid Arka Abhay × Arka Anamika has been directly attributed to increased number of fruits/plant during both climatic changes years. Therefore, their parents can be used in breeding programme for development of a new homogenous variety.